Human papillomavirus type 16 (HPV-16) E5 protein and HLA class I - MR Haghshenas; B Marchetti; M Saveria Campo; GH Ashrafi (Tehran University of Medical Sciences, 2005)
Human papillomavirus type 16 E5 protein (HPV16 E5) is expressed early in papillomavirus infection in the deep layers of the infected epithelium, and is localised primarily in the cell Golgi apparatus (GA) and endoplasmic reticulum (ER). We have shown that E5 prevents transport of the major histocompatibility class I (MHC I) to the cell surface and retains the complex in the GA. Here we show that these effects are due, at least in part, to the interaction between E5 and many types of MHC I heavy chain (Hc). In addition, we have further investigated the domain necessary to down-regulate surface MHC I and to interact with Hc, by using deletion mutants of E5, including either helical domain 1, 2 or 3. We show that the down-regulation of surface MHC I (HLA I in humans), and interaction with Hc are mediated by the first helical domain of E5. Although E5 down-regulates classical HLA selectively as it does not down-regulate non-classical HLA (ref. 4), the interaction with the Hc of classical HLA I is not specific for a particular type of HLA I, suggesting that E5 can interfere with antigen presentation by most, if not all, of classical HLA I types. The down-regulation of HLA I can potentially have serious consequences for the host immune response to viral infection, as the ability of infected cells to present antigenic peptides to effector T cells would be compromised.